RECONSTRUCTION OF PARATE EXECUTION MORTGAGE RIGHTS TO LAND BASED ON THE VALUE OF JUSTICE - Zaenal Arifin; Anis Mashdurohatun (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Credit risk in the context of financial institutions is a common occurrence but it has a negative impact if not insurmountable be influential on the soundness of the financial institution. Nevertheless, this risk can be managed and controlled, by way of precaution in terms of lending.1 Therefore, in the granting of credit, the bank must pay attention to the principles of lending right,2 which one of them is through the appraisal (coleteral) in the form of collateral that can be used as protection for creditors (financial institutions) in the event of default or breach of contract. Use of the mortgage institutions by financial institutions as collateral for the credit of the debtor for repayment of debt, considered more a sense of security in terms of lending, compared with provisions on the guarantee in the Civil Code in Article 1131. The weakness in terms of guarantees contained in the provisions of Article 1131 of the Civil Code is very different from the conception of the imposition of bail in the mortgage rights Act which guarantees the imposition of security rights institutions specifically tied and mutually exclusive because it applies only to one creditor only. This legal consequences on the situation in which if the debtor in default, mortgage holders creditors are entitled to sell the object as collateral through public auction in accordance with the provisions of the legislation in question with the right to precede rather than other creditors. Based the provisions of Article 6 of Law No. 4 of 1996 On Mortgage of Land And Objects Relating to Land (hereinafter referred to as UUHT). Takeover of collateral can be done by holders of mortgage without the need to seek prior authorization to the giver mortgag, and do not need to also ask for the establishment of a local court, if want to execute on mortgage as collateral the debt of the debtor in the case of debtor default.3 Mortgage holders may request to the  Head of Auction Office to the auction on the objects mortgage concerned,4 so this is a new step where before the execution of the deed grosse mortgages can only be done through the execution of the District Court.5 Execution of mortgage, this concept is known in the Code of Civil Code (hereinafter referred to as the Civil Code) is known as parate execution as referred to in Article 1178 of the Civil Code. Based these provisions, the takeover of the collateral in the form of a guarantee can be done by holders of mortgage (creditor) without the need for prior approval to the mortgage providers, when will be the execution of the mortgage which is a guarantee of debt of the debtor in which case the debtor is in default, this concept is known as parate execution which means that people refer to it as the execution is always ready at hand or parate execution.6 In practical implementation, execution parate implementation on the mortgage rights are not clear and even tend to stray far from the principles and doctrines parate execution. This is one of them can be seen in Article 14 paragraph (2) and (3) UUHT, where execution can be carried out on the certificate of mortgages in which includes irahirah with the words : “FOR THE SAKE OF JUSTICE UNDER THE ONE ALMIGHTY GOD”. Thus, the aforementioned phrase (irah-irah), indicates that the execution of the security object on the ground bound with mortgage understood as execution as grosse acte hypotheek. Other than that, on a general explanation Point 9 of the Act Mortgage stated that the concept of parate execution mortgage referred to in Article 14 paragraph (3) of the law still refers to Article 224 Herziene Indonesisch Reglement (hereinafter abbreviated as HIR). HIR provisions of Article 224 states that : The original letter from the letter of the mortgage and debt securities strengthened in front of a notary in Indonesia and whose head wear the words “On behalf of the Law”, equal magnitude with the judge’s decision, if the letter that should not be kept by peaceful means, then subject it to run held by the command and leadership from chairman of the district court which is in the jurisdiction the person who owes it silent or stay or choose a place of residence in the manner stated in the articles above in this section, but with the understanding that force the body can only be done, if it is allowed by the judge’s decision. If carrying out that decision to be executed at all or in part outside the area of the law courts the chairman ordered to run it, then the rules in Article 195 second paragraph and the next one followed. This condition caused multiple interpretations are not contradictory between Article 6 jo. Article 20 Paragraph (1) Clause (a) of the Act Mortgage, Article 14 paragraph (3) and Point 9 General Explanation Mortgage Act. This condition eventually making the principles of simplicity and legal certainty parate execution of mortgage not be achieved because eventually the creditor, in this case the holders of mortgage, can not run execution of mortgage easily, in accordance with the ideals of the establishment of the Act Mortgage as stated in the General Explanation of Mortgage Rights Act.